The International Criminal Court and Non-Party States - William A. Schabas (The Windsor Yearbook of Access to Justice, 2010)
Although more than half of the States in the world are parties to the Rome Statute of the International Criminal Court, more than eighty have yet to ratify. The article considers the relationship of the Court with these non-party States. It examines the exercise of jurisdiction over their nationals, arguing that international law immunities continue in force despite the terms of the Statute. Declarations of jurisdiction by non-party States are also studied, including the declaration formulated by the Palestinian Authority with respect to Gaza in January 2009. Nonparty States may be asked to cooperate with the Court and, where so ordered by the United Nations Security Council, they may be required to do this.